Accelerating Methane Reductions in Rice Production Systems through Market-based Mechanisms: Results of Farmer Surveys and Choice Experiments in Vietnam - Villanueva, Donald B.; Pajadan, Karen M.; Revicoy, Riela Rose R.; De Castro, Allenie M.; Malana, Xyla Mae L.; Gonzalez, Tobiah Rey P.; Pascual, Franz Josef E.; Nghia, Tran Dai; Hai, Le Trong; Mirzabaev, Alisher (International Rice Research Institute, 2025)
Vietnam is a major rice producer and exporter, with its rice paddies also being a significant source of methane emissions. This study surveyed 597 rice farmers across five provinces –Thai Binh (Red River Delta), Nghe An (North Central Coast), and An Giang, Kien Giang, Soc Trang (Mekong Delta) – to take stock of current practices and assess farmers’ awareness, adoption, and willingness to accept incentives for low-emission climate-smart agriculture (CSA) practices. The goal is to inform policies and investments that encourage farmers to adopt CSA, reducing methane emissions while improving farm productivity and livelihoods.